Prevalencia de hipertensión arterial y factores de riesgo en la población de 40 a 70 años que acude al Subcentro de salud – Capiro - Celi Pinto, Juana Rosario (2017)
Arterial Hypertension is the most chronic kidney disease known in the public health .One of the risk about these cardiovascular disease is the high blood pressure which affect millions of people around the world , it will provoke myocardial infarction and stroke .The researchers determined that nine billions of people died every year by hypertension in other case there are a lot people with disability . Determine the prevalence of arterial hypertension and its relation with risks factors over population about 40 and 70 years that call on the health subcenter in Capiro. We carry out a scientific method, descriptive and non-experimental trhough 331 adults that live in Capiro _ Piñas Town and take 159 adults for our researchs through which found 91 patients with arterial hypertension , where 46 belongs to male and 45 female . Looking the continue arterial hypertension in 159 patients only the 57,2 % have this desease and 42.8 % are not with this pathology .In summary the arterial hypertension has a high prevalence in the clients servedin the subcenter of capiro , according to the stadistics by the health organization there are 14% aproximately in the worldwide .The prevalence arterial hypertension is high and the most risks found were males acording to 45 and 60 years , hereditary factor , high levels of muscles mass , sedentism, bad eating habits and obesity